Analyzing a faculty learning community strategy based on a process-genre approach supported by videos to develop the writing competence of English teaching students. - Rojas, Viviana Alicia; Moya, Beatriz; Tagle, Tania; Campos, Monica; Ubilla, Lucia; Schuster, Cecilia (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2022)
The primary purpose of this inquiry is to analyze the impacts of a teaching and learning strategy designed and implemented by a Chilean Faculty Learning Community (FLC) intended to develop the writing competence of student-teachers of an English Teaching Program. The FLC-led strategy was implemented through an eight-step cycle based on the process-genre approach and supported by educational videos. FLC members guided this cycle during writing sessions at the four levels of the English Linguistic Competence course at Universidad Católica de Temuco. The FLC implemented this experience to address the challenge of serving diverse students’ learning needs and meet the requirements of the national English proficiency standards required by the Chilean Ministry of Education. The FLC examined this experience focusing on students’ writing tasks results and their perceptions of the use of videos in the process, oriented by an impact and evaluation framework of teaching innovations and an action research design. The ages of trainee English teachers who participated in this innovation range between 18 and 22 years old. Students’ writing tests results were analyzed and compared to the suggested CEFR outcomes per level. Moreover, students shared their perceptions towards the use of videos through focus groups. Results show that most students improved their writing performance, especially in content and organization. Furthermore, students perceived that videos helped them contextualize their writing process and contribute as a support resource embedded in classroom activities. Overall, this experience helped the FLC members identify changes resulting from the innovations and areas of improvement.